The Detecting Financial Statement Fraud With a New Fraud Diamond Model - Panji M Ghiffari; Fuad Fuad (Jurnal Proaksi, 2024)
The severe impact of financial statement fraud (FSF), particularly in large corporations, remains a significant challenge globally, often arising due to weak internal controls and the pressure on employees to meet financial targets. This study explores the applicability of the New Fraud Diamond Model on financial statement fraud (FSF) in energy companies listed on the Indonesian Stock Exchange (IDX) from 2019 until 2023. The sample comprises 238 companies selected through purposive sampling. The research results indicate that financial stability and financial targets positively influence FSF, while effective monitoring has a negative effect. Other variables show no significant impact. The findings provide practical implications for regulators and companies to strengthen governance mechanisms, enhance monitoring effectiveness, and align financial targets with long-term goals to mitigate fraud risks, thereby improving overall corporate accountability and financial market stability.